2014
DOI: 10.1111/jvim.12322
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Cycle Length and Atrial Size in Horses with and without Recurrence of Atrial Fibrillation after Electrical Cardioversion

Abstract: BackgroundAtrial fibrillation (AF) cycle length (CL) and atrial size have been used in humans to characterize electrical and structural remodeling to predict outcome of cardioversion of AF and risk for AF recurrence (rAF).HypothesisAtrial fibrillation cycle length can be determined in horses with AF, and AFCL and atrial size are related to risk for rAF.AnimalsEighteen horses with naturally occurring AF that were successfully converted to sinus rhythm (SR) by transvenous electrical cardioversion (TVEC).MethodsP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 28 publications
3
45
2
Order By: Relevance
“…The left atrium (LA) to aortic root (Ao) ratio in our foal was increased to 2.42 (reference value in adult horses: 1.04 ± 0.12; De Clercq et al . ), which confirmed left atrial dilation. Increases in left atrial volume and pressure may result in lung oedema.…”
Section: Discussionsupporting
confidence: 56%
“…The left atrium (LA) to aortic root (Ao) ratio in our foal was increased to 2.42 (reference value in adult horses: 1.04 ± 0.12; De Clercq et al . ), which confirmed left atrial dilation. Increases in left atrial volume and pressure may result in lung oedema.…”
Section: Discussionsupporting
confidence: 56%
“…AF induces electrical remodelling leading to AF stabilisation, both in human subjects and in horses [13,31]. However, if sotalol is to be used to suppress arrhythmias or to prevent AF recurrence, its effects might be different compared with healthy animals.…”
Section: Discussionmentioning
confidence: 99%
“…Reentrant circuits form more readily with larger atrial size, potentially due to the additional area available for rotor formation as demonstrated in computer modeling studies (278). Animal models (50, 123, 165), as well as clinical data support this idea (51,95,153). Atrial size may also indirectly affect tissue properties, since it can be a sign of increased atrial stretch, which is generally associated with increased tissue remodeling in the atria (108).…”
Section: Mechanisms Underlying Atrial Fibrillationmentioning
confidence: 84%